Implementasi Arsitektur Naratif Pada Ruang Di Museum Sepuluh Nopember - Purba, Khesia Rotua; Arfianti, Ami (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Museum Sepuluh Nopember in Surabaya is dedicated to commemorating the heroic events that occurred during the Battle of Surabaya in 1945. As a place that preserves and coneys this significant history, the museum holds a great responsibility to present a historical narrative that is not only informative but also impactful, capable of immersing visitors in the spirit and atmosphere of past events. This research aims to identify the application of narrative architecture in creating a spatial ambience that supports the stroytelling of history at the Museum Sepuluh Nopember. The research method involves direct observation, literature analysis on narrative architecture theory, and the museum’s interior design. The findings indicate that the use of narrative architectural elements such as spatial arrangement, lighting, materials, and layout design can significantly enhance the visitor experience and effectively support the delivery of historical stories.